Servicio post venta y satisfacción del cliente en tiendas de ropa del distrito de Contamana 2022 - Orbe Flores, Wendy Priscila (2023)
The development of this thesis, sought to determine the relationship between after-sales service and customer satisfaction in clothing stores in the District of Contamana 2022. Being the type of applied study and non-experimental design, a population of 1445 clients was also taken, from which a sample of 304 individuals was extracted, who were surveyed by means of two instruments. It was concluded that, the after-sales service in clothing stores in the District of Contamana is regular, because sometimes the store offered a discount, however, they have never allowed him to make changes of garments after his purchase, nor does he use social networks to contact his customers after the purchase. The level of customer satisfaction is medium (28%), because stores never know their interests and needs, sometimes they have observed improvements in the service offered, also, workers sometimes provide information and explanations for the acquisition of garments and sometimes have knowledge of the garments they offer. Finally, it was determined that there is a relationship between the study variables, contrasted by a coefficient of 0.830 and a significance of 0.000.